The basic function of М-class immunoglobulins (IgM) is permeability regulation of blood-tissue barrier for bacteria and its antigens - V. M. Perelmuter; Yu. N. Odintsov (Бюллетень сибирской медицины, 2005)
Function of antibodies IgM consists in regulation of permeability of a blood-tissue barrier for microorganisms and its antigenes. IgM production in philogenesis and in onthogenesis is the independent form of the immune response. IgM block invasion extracell parasitizing bacteria in tissue. Granulema formation is a variant of IgM function in regulation of permeability blood-tissue barrier for intracell parasitizing bacteria.The suggested hypothesis allows to use new approaches in therapy of infections with obligatory bacteriemia.